The Future of the profit split method - Danon, Robert J. (Alphen aan den Rijn, The Netherlands : Wolters Kluwer, 2021)
The Future of the Profit Split Method' is a thoroughgoing book elucidating the profit split method (PSM). Among the various transfer pricing methods, the OECD?s Base Erosion and Profit Shifting (BEPS) project provided substantial guidance on the PSM in 2018. In this compendium - the first book to analyse this increasingly adopted transfer pricing method - notable scholars and practitioners working in the international tax community express their views on the method, answering some unresolved questions and highlighting issues that are still open and pending, especially in light of the digitalization of the economy.
Includes bibliographical references and index.
Keywords: Transfer pricing -- Taxation -- Law and legislation; International business enterprises -- Taxation -- Law and legislation